Penerapan Prinsip Akad Wadiah Pada Tabungan Easy Wadiah (Studi Kasus Bank Syariah Indonesia Kantor Cabang Pembantu Bogor Ahmad Yani) - Ningsih, Sutiya; Abdul Syukur, R. Dudung; Faizal, Harun (CV. ITTC INDONESIA, 2026)
This study aims to describe the application of the wadiah contract principle in easy wadiah savings at the Ahmad Yani branch office of Bank Syariah Indonesia, identifying the advantages and disadvantages of easy wadiah savings products. The method used in this study is descriptive qualitative with a case study type of research. The data sources in this study were primary and secondary data, with data collection techniques including observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings of this study were based on interviews regarding the application of wadiah contracts. The results show that the procedure for implementing the wadiah contract in the Easy Wadiah savings product begins when an agreement is made between the two parties. It then describes that the implementation of the wadiah contract principle in Easy Wadiah savings at the Bogor Ahmad Yani branch office of Bank Syariah Indonesia has been implemented and carried out properly in accordance with the principles and provisions of sharia based on the Qur'an, and is in accordance with the MUI DSN Fatwa No.02/DSN-MUI/IV/2000 concerning savings that use the wadiah yad adh-dhamanah contract in the application of its products and is in accordance with PSAK 401 which regulates the presentation of sharia financial reports containing recognition, measurement, presentation, and disclosure. The advantages of easy wadiah savings are that they are free of administration fees, require an easy initial deposit to open an account, are affordable, are managed based on sharia principles, and funds can be withdrawn at any time. The disadvantages of the Easy Wadiah savings account are that there is no profit sharing, it is not suitable for customers who want to invest, and there are no bonuses. The limitations of this study are that it concerns the application of the wadiah contract principle in the Easy Wadiah savings account.